Effects of Construction Materials to Achieve Sustainable Buildings - Mohanad I. Altuma; Redvan Ghasemlounia (International Journal of Engineering and Management Research, 2021)
This paper pursues to study the challenges to applied sustainable building resources in building construction and to evaluate the factors influencing the choice of construction materials with respect to the concepts of sustainability. The research purpose was accomplished in two parts; in the first part, a conceptual study to establish the reasons why sustainable building resources are restricted usage in construction, and in the second part a conceptual study on sustainable building resources and their properties. In order to encourage sustainability in design and construction, several countries have developed an understanding of sustainable development for buildings. In order to decrease the negative environmental effects of buildings, the construction industry has created sustainable building approaches, where buildings play an important role in greenhouse gases, massive energy, and water use and large land use are important. Ecological design involves designing houses, offices, or other facilities in a way that decreases the ecological impact, that means sustainable buildings, Where the careful equilibrium among economic, environmental, and social well-being of the currency and communities and therefore of the earth looks to sustainability at current. In order to evaluate the degree of sustainability practices, sustainability evaluation systems were established for effective performance at the top level of qualified systems. In sustainable buildings, accredited standards and checklists will be planned, built, and run.